Serial Murder of Four Victims, of Both Genders and Different Ethnicities, by an Ordained Baptist Minister - Reavis, James A. (Case Reports in Psychiatry, 2011)
A case of a 61-year-old African-American male who sexually assaulted and murdered four individuals, of different ethnicities and both genders, is reported. The subject additionally engaged in sexual activity with each victim postmortem. Each murder is reviewed in detail, and the subjective state of the offender during the murders is commented upon. Psychological test data are reviewed. The subject met criteria for several Axis I disorders, including Bipolar I Disorder, Pedophilia, and Sexual Sadism, and met criteria for Axis II diagnoses of Narcissistic and Antisocial Personality disorder. He was additionally classified as a Psychopath, which, in combination with his Sexual Sadism, general psychiatric state, and exquisite sensitivity to humiliation, led to his decision to murder.